Knowledge and Attitudes Not Strongly Related to COVID-19 Prevention, Behaviors, and Vaccination Among Filipino College Students - Gefilloyd L. De Castro; Abee M. Eijansantos; Nuriza P. Jalani; Joni Czarina P. Amora; Gualberto A. Lantaya Jr. (Asian Journal for Public Opinion Research)
The effects of the COVID-19 pandemic across various sectors are far-reaching, and the education sector is not an exemption. Approved and recognized vaccines are clinically proven to provide protection and have been considered one of the primary mitigations against the virus. Knowledge, attitude, and related practices (henceforth KAP) toward the virus is widely considered to be an essential cognitive key in public health for health intervention, prevention, and promotion. Previous studies revealed a positive correlation between knowledge and attitude. This study investigated the KAP and their relationship among the 857 college students in one state college in the Philippines using an online survey. Using descriptive statistics, the findings showed that the majority of the respondents have been fully vaccinated against COVID-19. Respondents were shown to be knowledgeable about COVID-19, specifically about its transmission, clinical symptoms, treatment, risk groups, isolation, prevention, and control. Positive attitudes toward individual and governmental mitigation and control of the virus were shown. Their scores on practices revealed that they always exhibit protective and preventive behavioral practices. Pearson correlation revealed a weak significant relationship between knowledge and practice, and a fair significant relationship between attitude and practice. No significant relationship is found between knowledge and attitude. This study hopes to find its place in the literature worthy of consideration as empirical support toward understanding a specific group's perceptive risk and preventive behavior toward the virus, policy making, and health intervention and promotion.